2015
DOI: 10.1038/nphys3357
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of the exciton binding energy and effective masses for charge carriers in organic–inorganic tri-halide perovskites

Abstract: Solar cells based on the organic-inorganic tri-halide perovskite family of materials have shown significant progress recently, o ering the prospect of low-cost solar energy from devices that are very simple to process. Fundamental to understanding the operation of these devices is the exciton binding energy, which has proved both di cult to measure directly and controversial. We demonstrate that by using very high magnetic fields it is possible to make an accurate and direct spectroscopic measurement of the ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

117
1,477
6
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,761 publications
(1,643 citation statements)
references
References 33 publications
117
1,477
6
5
Order By: Relevance
“…Frost et al estimated the binding energy of excitons in this system to be about 0.7 meV -too small to affect significantly the photovoltaic performance [16]. This is in contradiction with experimental evidences that indicate a value in the range 6-55 meV [5,37,[67][68][69][70][71][72]. Solutions of the Bethe-Salpeter equation for a single molecular orientation revealed huge exciton binding energies of 153 meV for the cubic phase [39] and 40 meV for the tetragonal phase [32].…”
Section: Discussioncontrasting
confidence: 45%
“…Frost et al estimated the binding energy of excitons in this system to be about 0.7 meV -too small to affect significantly the photovoltaic performance [16]. This is in contradiction with experimental evidences that indicate a value in the range 6-55 meV [5,37,[67][68][69][70][71][72]. Solutions of the Bethe-Salpeter equation for a single molecular orientation revealed huge exciton binding energies of 153 meV for the cubic phase [39] and 40 meV for the tetragonal phase [32].…”
Section: Discussioncontrasting
confidence: 45%
“…This approximation misses the Wannier excitons below the band edge, but they are very shallow. 27,28 If the potential is local,…”
Section: -4mentioning
confidence: 99%
“…Conversely, the electronic polarizability of covalent solids generally results in a high electric susceptibility and an efficient screening of the Coulomb interactions between carriers. Now, numerous studies have yielded values of the exciton binding energy in perovskites and, although results show a great variability, they all converge to surprisingly low values of 2-60 meV for CH 3 NH 3 PbI 3 and up to 150 meV for CH 3 NH 3 PbBr 3 , [17][18][19][20][21][22][23] indicating that mostly free carriers are generated at room temperature. In addition, it has been shown that the precise character of the photogenerated carriers, as well as the ratio of free carriers to bound electron-hole pairs are highly dependent upon the nanostructuring of the material.…”
Section: Eas Of Molecules or Confined Excitonic Statesmentioning
confidence: 99%